Effects of microbivorous nematodes on microbial necromass accumulation under changing precipitation in tropical forests - Qiongjie He; Ning Zhao; Kangle Hou; Qiang Ran; Rentao Liu; Faming Wang; Feng Sun; Yakov Kuzyakov (Applied Soil Ecology, 2026)

Effects of livestock grazing on soil nematodes vary with soil depth in a temperate forest - Zhen Zhao; Jialing Teng; Xintong Wei; Jiawei Feng; Tianming Wang (Applied Soil Ecology, 2026)

Environmental and Biological Factors Shaping Fish Swimming Ability: Insight From a Meta‐Analysis on Endemic Fish in China - Yuanming Wang; Hongtao Wang; Pengcheng Li; Xintong Li; Ruifeng Liang; Kefeng Li (Reviews in Aquaculture, 2026)
Fish swimming ability serves as a robust proxy for physiological assessment and species conservation. Numerous rivers with a large spatial span and diverse fish species in China complicate the efforts to understand swimming ability and challenge the protection of fish populations. One hundred and sixty‐four relevant studies over the past 15 years, involving 30 families and 126 distinct test sites, were identified to provide a comprehensive overview of fish swimming ability in China. Specifically, test sites geographically concentrated in the Yangtze River basin and Cyprinidae received the most research attention. The basin, family, altitude, living condition, and body length exerted considerable effects on fish swimming ability. Fish from the continental basin had the highest induced swimming speed ( U ind ), whereas those from the southwest basin showed outstanding critical ( U crit ) and burst ( U burst ) swimming speeds. U ind did not differ significantly at the family level, while Cyprinidae and Cobitidae outperformed other families in U crit and U burst . U ind was lowest at an altitude of 2328–3588 m, while U crit and U burst followed unimodal trends, peaking at altitudes of 622–1343 m. Test apparatus and protocols had a limited effect on fish swimming ability, only except that swimming speeds in Brett‐type flumes were higher than that in pipe channels or straight flumes. The living condition did not affect U ind while wild Cyprinidae exceeded cultured Cyprinidae in U crit and U burst . Overall, this study identified factors contributing to fish swimming ability differences and their variation patterns, deepening our knowledge on fish swimming ability and informing fish conservation strategies in China.

A long-term high-resolution national assessment of N2O emissions from Chinese lakes and reservoirs - Jing Wei; Huixiao Pan; Yunjie Zhang; Wenping Yuan; Hongtao Duan; Lishan Ran; Xiuzhi Chen; Faming Wang; Zhangcai Qin; Shilong Piao (Science China Earth Sciences, 2026)

Linking habitat connectivity to trophic structure: stable isotopic insights from resident and transient consumers in estuarine mangrove wetland - Xiaoyan Lu; Yuming Wang; Zhenxiong Yang; Hui Chen; Guanmin Huang; Jianxiang Feng (Ocean & Coastal Management, 2026)

Balancing conservation and fisheries: A dual-model framework for seagrass spatial planning in the Yellow Sea and Bohai Sea, China - Ming Wang; Yanmei Ding; Shuai Yang (Ocean & Coastal Management, 2026)

Positive effects of using Bacillus velezensis BJCP3 and Aspergillus spinosus ISP018 on soil microbial community and peanut growth in acidic red soil - Zhiwei Yang; Xiaoqian Yang; Pan Wu; Qingqing Hua; Shuang Peng; Yiming Wang (Applied Soil Ecology, 2026)

Conversion of croplands to wetlands repartitions nitrogen loss pathways by altering substrate availability - Xiaokun Yu; Tingyu Fan; Hongzhi Xiang; Liangji Xu; Shun Wang; Xingming Wang; Bing Li; Changde Yang (Applied Soil Ecology, 2026)

Sustainable land use and agricultural management enhance arbuscular mycorrhizal fungal communities and soil health - Huaisong Wang; Juntong Zhu; Mingming Wang; Lei Zhang; Ying Gao; Lianxuan Shi; Jixun Guo; Rui Guo; Tao Zhang (Applied Soil Ecology, 2026)

Effects of hummock–hollow microtopography on soil microbial communities and their links to soil carbon cycling in a sedge peatland of the Changbai mountains - Biyu Shi; Ming Wang; Guodong Wang; Xingli Li; Tao Zhang (Applied Soil Ecology, 2026)

Climate and soil nutrients jointly affect the variations in microbial nutrient limitation with elevation in sedge peatlands - Tao Zhang; Yimeng Wang; Ming Wang; Shengzhong Wang; Guodong Wang; Meiling Zhao; Jingci Meng; Yusong Yuan; Nanlin Hu (Applied Soil Ecology, 2025)

Breaking the legume intensification paradox: Precision nitrogen-phosphorus fertilization for optimizing biological nitrogen fixation, yield, and soil physicochemical properties in mung bean - Jiahao Ge; Qi Wang; Enlei Li; Siyuan Zhang; Xaioyi Han; Shaofei Li; Qixuan Wang; Qingming Wang; Pengyue Wu; Feng Gao; Baili Feng; Jinfeng Gao (Applied Soil Ecology, 2025)

Phosphorus fertilizer input level regulates soil organic carbon physical fraction sequestration by influencing the microbial community - Zheng Ni; Minghui Cao; Yuming Wang; Wenling Zhong; Mengxia Zhang; Yan Duan; Lifang Wu (Applied Soil Ecology, 2025)

Recovery of bacterial network complexity and stability after simulated extreme rainfall is mediated by K−/r-strategy dominance - Yin Wang; Mengjun Qu; Jianming Wang; Weilin Zhu; Jingwen Li (Applied Soil Ecology, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Estimating spatiotemporal dynamics of evapotranspiration and assessing the cause for its increase in China - Wenjing Yang; Yong Zhao; Huade Guan; Yingfu Tang; Mingming Yang; Qingming Wang; Jianshi Zhao (Agricultural and Forest Meteorology, 2023)

Influences of desiccation, submergence, and salinity change on survival of Ligia cinerascens (Crustacea, Isopoda): high potential implication for inland migration and colonization - Peng Zhang; Jingxian Sun; Shiming Wang; Dongdong He; Li Zhao (Hydrobiologia, 2016)

Transplantation of Icefish ( S alangidae) in C hina: Glory or Disaster? - Bin Kang; Junming Deng; Zhongming Wang; Jie Zhang (Reviews in Aquaculture, 2015)
China has a long history of aquaculture, and it contributes the largest aquaculture production worldwide. Aside from expanding aquaculture area and maximizing unit yield, introducing new potential species is greatly encouraged. Icefish ( S alangidae) from T aihu L ake have been introduced into other lakes and reservoirs throughout the country since 1979. Neosalanx tangkahkeii was introduced into the southern part of C hina, and P rotosalanx chinensis was introduced into the northern part of C hina, and both species have been introduced into a small part of central C hina and Y unnan P rovince in southwest C hina. Only one‐third of the transplantation was successful, and most of their yields experienced a burst‐down course. Intrinsic traits of icefish including annual life cycle, higher fecundity, lower trophic level, together with sufficient environment capacity supported the population forming and burst, while overfishing, pollution and short of food could result in the failure of the transplantation. The introduction of icefish brought in economic benefits, but severely threatened biodiversity, especially in plateau lakes in Y unnan P rovince, caused possible hybridization and carried diseases. According to different environmental conditions and economic needs at regional scale, further transplantation of icefish would face respective fate as resource conservation, rapid development, limitation and insignificance. Increasing attentions on environmental protection and sustainable resource utilization require a fresh evaluation and adjustment of icefish transplantation to achieve an ecologically healthy aquaculture.